Thymus species in Ethiopia: Distribution, medicinal value, economic benefit, current status and threatening factors - Damtie, Destaw; Mekonnen, Yalemtsehay (Ethiopian Journal of Science and Technology, 2025)
The genus Thymus is one of the genera in the family Lamiaceae. In Ethiopia, it is represented by two endemic species namely Thymus serrulatus and Thymus schimperi. The aims of this study were to identify the types of species from six geographically distant localities in Ethiopia, assess the ethnobotanical and socioeconomic information of these species in these localities and gather information about the current status and threatening factors of these species in the six localities. The plant specimens from these localities were authenticated by experts in the National Herbarium of Addis Ababa University as Thymus serrulatus and Thymus schimperi. The plants were rated by local informants as treatments for ailments like blood pressure (30.7%), general pain syndrome (10%), influenza (10%), abdominal pain (10%), ascariasis (2.9%), and intestinal parasites (2.9%). The informants rated the economic value of these plants as animal forage (71.5%), bee forage (71.5%), condiments (68%), and washing and fumigation (46%). According to the informants, the status of Thymus species is declining from time to time due to overgrazing (80.7%), agricultural expansion (64.2%), overharvesting (48.57%), uprooting during harvesting (14.2%), and lack of recognition (13.6%).